Предмет: Алгебра,
автор: Arbekovskaya
(x-6)²-x(x+8)=2
(2y+1)²-4y²=5
y(y-1)-(y-5)²=2
16y(2-y)+(4y-5)²=0
найдите корень уравнения
Ответы
Автор ответа:
0
1) (x-6)²-x(x+8)=2
x² - 12x + 36 - x² - 8x = 2
-20x = - 34 : (-20)
x = 1,7
2) (2y+1)²-4y²=5
4y² + 4y + 1 - 4y² = 5
4y = 4 | : 4
y = 1
3) y(y-1)-(y-5)²=2
y² - y - y² + 10y - 25 = 2
9y = 27 | : 9
y = 3
4) 16y(2-y)+(4y-5)²=0
32y - 16y² + 16y² - 40y + 25 = 0
-8y = -25 | : (-8)
y = 25/8 = 1 3/8
x² - 12x + 36 - x² - 8x = 2
-20x = - 34 : (-20)
x = 1,7
2) (2y+1)²-4y²=5
4y² + 4y + 1 - 4y² = 5
4y = 4 | : 4
y = 1
3) y(y-1)-(y-5)²=2
y² - y - y² + 10y - 25 = 2
9y = 27 | : 9
y = 3
4) 16y(2-y)+(4y-5)²=0
32y - 16y² + 16y² - 40y + 25 = 0
-8y = -25 | : (-8)
y = 25/8 = 1 3/8
Похожие вопросы
Предмет: Алгебра,
автор: miich31
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: sound06
Предмет: Биология,
автор: Lalala3510